The Hadith of Gabriel: The Adab of Learners and Educators in Learning - Ahmad Maulana (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2022)
The Hadith of Gabriel is a hadith that contains a description of the learning process involving the Prophet Muhammad, the Angel Gabriel, and the companions of Prophet Muhammad. Various components of learning such as materials, methods, and islamic ethics can be seen both explicitly and implicitly in this hadith. This study aims to determine the adab of learners and educators contained in the Hadith of Gabriel. This literature study uses the content analysis method. The result of research from the understanding of this hadith is that learners should wear good clothes, come to science even though the distance is far, glorify educators and science, study directly to competent educators, have interest and perseverance in learning, not shy to ask, help each other learners, choose subjects from the most important, and not answering questions with “I already know” answers. Meanwhile, as an educator should be humble, not shy to say “I don`t know”, and using right methods in teaching